2017
DOI: 10.1002/asia.201700922
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation‐Induced Emission Characteristics of o‐Carborane‐Functionalized Tetraphenylethylene Luminogens: The Influence of Carborane Cages on Photoluminescence

Abstract: Tetraphenylethylene (TPE)-carborane hybrids are constructed, and the impact of carborane substituents on the aggregation-induced emission (AIE) characteristics of TPE-cores has been investigated. When altering the 2-R-group on the carborane unit with -H, -CH or phenyl group, the luminescent quantum yield of the corresponding TPE derivatives can be manipulated from 0.18 to 0.63 in the solid state. The emission color exhibits an obvious 100 nm shift (from blue to yellow).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
29
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 53 publications
3
29
0
Order By: Relevance
“…Remarkably, this is, to the best of our knowledge, the first example of an excimer species involving a carborane with ICT character. Secondly, and in line with many similar carborane‐containing fluorophores,13, 14, 15, 17, 18, 19, 20, 22, 31, 32 the AIE observed for 2 is the result of a unimolecular ICT species. These two points may also be used to rationalize the differences between the emission efficiencies recorded from the two long‐wavelength emissions.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…Remarkably, this is, to the best of our knowledge, the first example of an excimer species involving a carborane with ICT character. Secondly, and in line with many similar carborane‐containing fluorophores,13, 14, 15, 17, 18, 19, 20, 22, 31, 32 the AIE observed for 2 is the result of a unimolecular ICT species. These two points may also be used to rationalize the differences between the emission efficiencies recorded from the two long‐wavelength emissions.…”
supporting
confidence: 69%
“…These ICT states are notable for their flexible carboranyl C−C bond, which can vibrate and relax non‐radiatively, or radiatively with a highly red‐shifted emission 24, 25, 26, 27, 28, 29, 30. Such systems often exhibit aggregation‐induced emission (AIE),13, 14, 15, 17, 18, 19, 20, 22, 31, 32 that is, in an aggregated state where molecular motion is restricted, non‐radiative relaxation pathways from the ICT state are inhibited, leading to a significant increase in emission efficiency. It has been demonstrated that incorporation of bulky carboranes on the long edges of linear acenes creates a large steric hinderance between the carboranes and proximal protons, leading to a considerable deformation of the ring system 15, 16, 17.…”
mentioning
confidence: 99%
“…Even though intense luminescence can be observed in the solution state, optical properties were often spoiled through ACQ by intermolecular interactions in the solid state. [5][6][7] It has been reported that some of the o-carborane [8][9][10][11][12][13] derivatives presented AIE [14][15][16][17][18][19][20][21] and can be applied as a solid-state luminescent material. [1][2][3] Intense solid-state luminescent properties originating from AIE were found and applied for developing the conjugated materials, including polymers.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, applicability of the modified o -carboranes for organic light-emitting devices has been demonstrated from the recent studies [ 30 , 31 ]. Moreover, it should be noted that some of the modified o -carboranes also showed AIE [ 23 , 24 , 30 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. In the solution state, the modified o -carboranes presented slight emission as a result of emission annihilation by molecular motions, while intense emission was recovered because of low mobility in the solid state.…”
Section: Introductionmentioning
confidence: 99%